2019
DOI: 10.7554/elife.46973
|View full text |Cite
|
Sign up to set email alerts
|

Sensing how to balance

Abstract: How does the inner ear communicate with the cerebellar cortex to maintain balance and posture?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Therefore, these opposed polarities may couple centrally as activation/disinhibition, which may sharpen tuning, and increase sensitivity of the vestibular nuclei to natural stimuli. Furthermore, Maklad and Fritzsch (2003) and Maklad et al (2010) demonstrated in mice that hair cells of one polarity outside the striola projects almost exclusively into the cerebellum, whereas the other polarity medial to striola projects to the brainstem, a finding recently supported by detailed physiological and connectional investigation of canal cristae (Ango & Dos Reis, 2019;Balmer & Trussell, 2019). The cerebellum, with its inhibitory Purkinje cells projecting to the vestibular nuclei, may provide another layer of cross-striolar inhibition (Balmer & Trussell, 2019;Maklad et al, 2010).…”
Section: Physiological Considerationsmentioning
confidence: 88%
“…Therefore, these opposed polarities may couple centrally as activation/disinhibition, which may sharpen tuning, and increase sensitivity of the vestibular nuclei to natural stimuli. Furthermore, Maklad and Fritzsch (2003) and Maklad et al (2010) demonstrated in mice that hair cells of one polarity outside the striola projects almost exclusively into the cerebellum, whereas the other polarity medial to striola projects to the brainstem, a finding recently supported by detailed physiological and connectional investigation of canal cristae (Ango & Dos Reis, 2019;Balmer & Trussell, 2019). The cerebellum, with its inhibitory Purkinje cells projecting to the vestibular nuclei, may provide another layer of cross-striolar inhibition (Balmer & Trussell, 2019;Maklad et al, 2010).…”
Section: Physiological Considerationsmentioning
confidence: 88%
“…The vestibular system connects with the vestibular ganglion, which sends primary afferents directly to the cerebellum and secondary afferents to the vestibular nuclei. Primary and secondary afferents synapse with unipolar brush cells within the cerebellum, which connect with granule cells that ultimately contact Purkinje cells ( Ango and Dos Reis, 2019 ). Interestingly, Zanin et al (2016) showed that the conditional deletion of p75NTR only in cells from the external granule layer recapitulate the balance defect observed in the p75NTR ExonIII KO.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, vestibular nuclei also engage the oculomotor areas of the vermis (lobules V-VII) (82) while processing direct input from the mesencephalic trigeminal nucleus that processes proprioceptive information from extraocular and neck muscles to control eye-head coordination (134) and from periodontal ligaments to coordinate mastication (133). As expected, damage to flocculo-nodular and adjacent portions of the vermis, such as the uvula, can cause vertigo and extreme disturbance of equilibrium, head and body posture, and ocular movements (144,145).…”
Section: Axonal Input To the Cerebellummentioning
confidence: 96%